An ex-ante cost-benefit assessment of the possible Energy Efficiency Obligation Scheme in Türkiye - Cin, Rabia; Onaygil, Sermin; Gokcek, Tayfur (ELSEVIER SCI LTD, 2024)
T & uuml;rkiye has aimed to adopt the Energy Efficiency Obligation Scheme (EEOS) as one of its national energy efficiency goals since 2018. However, the implementation date has been constantly postponed. This study aims to evaluate the future of a possible Turkish EEOS with actual energy and cost data and to provide an example to all scheme participants, especially policymakers. In this study, a basic Turkish EEOS structure, in which incumbent electricity suppliers are obligated parties and industry and commercial buildings are end-users, is created with its cost and benefit items. An ex-ante cost-benefit assessment of Turkish EEOS is conducted by applying a two-level distributed optimization approach where obligated parties and end-users have their own objective functions and focus on their goals without interfering with the other levels. Case studies were created by changing the obligation rates, the EEOS fee rates, and the penalty amounts. In the end, it is revealed that the Turkish EEOS can fully finance itself with a win-win approach under fair EEOS fee rates. The penalty mechanism is important to obligated parties to fulfill their obligations. After discussing the analysis results and the sensitivity analysis, policy implications and practical recommendations were developed for T & uuml;rkiye.
Keywords: Energy efficiency obligations; Distributed optimization; Multivariate analysis of variance; Turkish energy efficiency policy; Business & Economics; Energy & Fuels; Environmental Sciences & Ecology